Tolerance and Social Harmonization of The Hindu Islamic Community of The Tengger Tribe in Eid Al-Fitr And Nyepi - Hasan Assidiqi, ali; Barizi, Ahmad; Mustofa, M. Lutfi (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2024)
Indonesia is known for its many kinds of differences. Behind the friction that occurs, there are also many exemplary differences because they are able to create tolerance and social harmony of a strong community such as Islam and Hinduism in the Tengger Tribe. The purpose of this study is to provide an overview of the importance and practice of tolerance and harmonization between Islam and Hinduism that needs to be emulated through religious activities such as Eid al-Fitr and Nyepi Day. This study uses a qualitative type of anthropological approach by collecting the main data sources from interviews with three Islamic religious leaders, five Hindu religious leaders, and seven communities. Secondary data sources from books, and other papers and analyzed using B Miles and Huberman's theory. The results show that 1) the tolerance and harmonization of the Hindu Islamic community in the tengger tribe towards Eid al-Fitr worship is very strong. For example, during fasting, the Hindu people prefer to hide their food, when breaking the fast there are some who distribute free takjil and some participate in selling takjil. Every night of worship with hadrah never disturbed them. During holidays, they tend to help secure the course of worship by becoming a parking attendant and making their yard a parking lot or worship. 2) Likewise, the tolerance and harmonization of the Hindu Islamic community towards the Nyepi holiday worship is also well seen. For example, during the Nyepi celebration, Muslims also participate by limiting all activities including work and going out of the house so that they do not use lights or something shiny like Hindus do during Nyepi. During the food banquet, when Hindus invite, Muslims follow it well. In the analysis of Max Weber's theory of action, the Islamic and Hindu societies do all of this because they have a goal for the future good, which is known as instrumental rational action, and because they follow their parents and ancestors who are known for traditional actions. The next research recommendation is to focus on using quantitative research to determine the influence of worship or religious activities on the tolerance and harmonization of the Tengger ethnic group.